Creative Ecologies: Derek Walcott’s Postcolonial Ecopoetics - Emma Trott (Forum, 2013)
This essay explores the centrality of Derek Walcott’s poetics of nature to his creative imagination. Forensic attention to language illustrates how connections between the mind and its environments engage critical work at the intersection of ecocriticism and postcolonialism. Poetry’s contribution to a resolution of these discourses’ conflicting concerns is revealed, in a fresh analysis of Walcott’s poetic ecology.